2016
DOI: 10.1186/s12889-016-3388-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection awareness, vaccine perceptions and uptake, and serological profile of a group of health care workers in Yaoundé, Cameroon

Abstract: BackgroundCameroon is one of the countries in Africa with the highest burden of Hepatitis B infection. Health care workers are known to be at risk of occupational exposure to blood and other infectious bodily fluids. The aim of this study was to assess the profile of serological markers of hepatitis B virus (HBV) infection, knowledge and perceptions regarding HBV infection among health care workers in a health area in Yaoundé.MethodsA cross-sectional study was conducted in the Mvog-Ada Health Area of the Djoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 24 publications
10
64
5
2
Order By: Relevance
“…Similar results have been reported by Abdela in Ethiopia [19] and Al Wutayd in Saudi Arabia [20]. However, other authors have reported a higher level of knowledge among students over 25 years of age in Laos [21] and among men in Cameroon [8]. We also did not find any variation in levels of knowledge between the different fields of study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have been reported by Abdela in Ethiopia [19] and Al Wutayd in Saudi Arabia [20]. However, other authors have reported a higher level of knowledge among students over 25 years of age in Laos [21] and among men in Cameroon [8]. We also did not find any variation in levels of knowledge between the different fields of study.…”
Section: Discussionsupporting
confidence: 91%
“…This result is significantly lower than that reported by Kumar in India (80.1%) [7]. According to the literature [8,9], the main transmission routes of HBV (blood: 86.3%; sexual intercourse: 80.2%; motherto-child: 66.2%) were identified by our participants. However, 19.4% of students reported that HBV could be transmitted by the fecal-oral route.…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly, studies from different areas reported the same finding [20, 22, 37, 38]. Another barrier mentioned was vaccine unavailability, which was reported by 36% of participants.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have already revealed a lower knowledge on hepatitis B in general population, medical stu-dents, and patients (8)(9)(10)(11). One study from China also investigated Chinese physicians' awareness regarding the 2010 guidelines on the treatment of CHB.…”
Section: Discussionmentioning
confidence: 99%